KARTEL PENETAPAN HARGA DAGING SAPI DALAM PERSPEKTIF HUKUM PERSAINGAN USAHA - Ade Darmawan Basri (Wacana Hukum, 2019)
This study discusses the Cartel in beef pricing, because of the proliferation of malpractice who seek profits by making agreements to control production and or services that result in other business actors not being able to enter into the same business competition for goods and services and the many losses they cause. This research is a normative legal research, and uses various approaches to problems, namely by using statue approach, conceptual approach, and case approach. The results showed that the case Number 10 / KPPU-I / 2015 showed that import companies had made an agreement to hold the supply of cattle, whereas the one who gave the policy was the government which cut cattle imports from 200,000 birds per 2015 to 50,000 heads, while in In 2015 the government estimated that the needs of cows up to 4 million, namely 20% or 750,000 were supplied through imports, so the impact was the reduction of cattle imports by 150,000, the implication being that the supply decreases causing a surge in prices.